Did he or didn’t he? Mixed evidence for the continued influence of retracted misinformation on person impressions - Amy J. Mickelberg; Bradley Walker; Ullrich K. H. Ecker; Piers D. L. Howe; Andrew Perfors; Nicolas Fay (PLoS ONE, 2025)
Retracted misinformation often continues to influence event-related reasoning, but there is mixed evidence that it influences person impressions. A recent study found no evidence for the continued influence of retracted misinformation on person impressions across four experiments. However, the study used a dynamic impression-rating measure that may have obscured any continued influence effects. Here we report three experiments that tested for the continued influence of retracted misinformation on person impressions using a non-dynamic impression-formation task that is comparable to tasks used in event-related misinformation research. Participants formed an impression of a fictitious person based on a series of behaviour statements. A negative behaviour statement (e.g., “John kicked his pet dog hard in the head when it didn’t come when called”) was subsequently retracted or not retracted. Evidence for the continued influence of the retracted behaviour statement was found in one experiment; in the other two experiments the retracted misinformation was fully discounted. The mixed findings indicate that, unlike retracted event-related misinformation, retracted person-related misinformation does not consistently show a continued influence effect. Future research should investigate potential moderating factors, such as the attributes of the misinformation and the presence of social-category information about the protagonist, to reveal the mechanisms underlying the continued influence effect in person impressions.